ANANGIA, A NEW MONOTYPIC GENUS OF CUCURBITACEAE FROM EAST MOLUCCAS - W.J.J.O. De Wilde; Brigitta E. E. Duyfjes; RWJM Van Der Ham (BRIN Publishing (Penerbit BRIN), 2006)
DE WILDE, W.J.J.O; DUYFEES, B.E.E. & VAN DER HAM, R.W.J.M. 2006. Anangia, a new monotypic genus of Cucurbitaceae from East Moluccas. Reinwardtia 12(3): 219 – 222.– A new monotypic genus of Cucurbitaceae from Morotai (Indonesia) is described. The genus is defined by unique characters, including large sepals, much longer than the petals, and it has distinctly cucurbitoid pollen features. The only species is Anangia macrosepala W.J. de Wilde & Duyfjes.